(untitled) (Academia Journal of Medicine, 2021)
Background: Cardiovascular disease (CVD) is the commonest cause of natural death all over the world. Asians develop this disease nearly one to two decades earlier than the Western population. Though CVD does not always lead to immediate death yet may be associated with delayed mortality or morbidity leading to significant loss of productivity of an individual. Hence, it becomes imperative to assess clinical parameters that may not only prevent death but also helps in reducing morbidity. Hyponatremia is found to be one of the major causes of sudden as well as delayed deaths in patients experiencing acute myocardial infarction (AMI). As serum sodium estimation is an easy, inexpensive, and routine laboratory investigations performed in patients with AMI, we aimed to assess its prevalence and prognostic significance in such patients. Subjects & Methods: One hundred patients of AMI admitted in the Department of Medicine of our institution were enrolled in our study according to inclusion & exclusion criteria following approval from IEC. Serum sodium levels of all patients were recorded at the time of admission, at 48hours and at one month. All patients underwent ECG and echocardiography for assessment of their cardiac function as well as subgrouping into STEMI/NSTEMI. All patients were followed up for signs of congestive cardiac failure, arrhythmias & cardiogenic shock or death. The above data was analyzed with appropriate statistical tests. Results: In our study, 38 patients developed hyponatremia, 13 at the time of admission, 15 at 48hours and 10 at one-month time. Out of 62 patients with normal sodium, 9 developed CCF, 9 arrhythmias and 4 died. On the other hand, nearly 25 patients with hyponatremia developed CCF and 11 patients died. This showed that AMI patients with hyponatremia have poor outcome. Conclusion: There is significant occurrence of hyponatremia, patients of acute MI. Occurrence of hyponatremia in patients of acute myocardial infarction is associated with adverse cardiovascular outcomes viz. arrhythmias, congestive cardiac failure and death. Also, the occurrence of these adverse efect is directly correlated the severity of hyponatremia. Hence, serum sodium can be used as simple and effective tool for risk assessment in patients of acute myocardial infarction.